2016
DOI: 10.1021/acs.analchem.6b00590
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Analysis of Lung Tumor Cell Lines: Implementation of an Invasiveness Scale Based on the Cell Infrared Signatures

Abstract: Assessing the tumor invasiveness is a paramount diagnostic step to improve the patients care. Infrared spectroscopy access the chemical composition of samples; and in combination with statistical multivariate processing, presents the capacity to highlight subtle molecular alterations associated with malignancy development. Our investigation demonstrated that infrared signatures of cell lines presenting various invasiveness phenotypes contain discriminant spectral features, which are useful informative signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The data analysis of Gaydou et al is in contrast with our approach since we filtered the spectra instead of correcting them [19]. Due to filtering, the number of spectra was reduced, however, the number of spectra remained unchanged during correction, while some wavelength values were modified by the EMSC algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data analysis of Gaydou et al is in contrast with our approach since we filtered the spectra instead of correcting them [19]. Due to filtering, the number of spectra was reduced, however, the number of spectra remained unchanged during correction, while some wavelength values were modified by the EMSC algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Gaydou et al took mid infrared imaging as a tool to investigate cell lines according to their infrared signature [19]. The cells were fixed in formalin and embedded into paraffin after centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PLS-based approach employed to construct the predictive model can also provide the vibrational markers of the aggressiveness scale. Indeed, from the PLS regression vectors it is possible to identify infrared features involved in the scale 51. Since the infrared signals are of multivariate nature, several vibrations assigned to different chemical groups ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sarkar et al 212 observed stimulated epithelial-to-mesenchymal transition of lung normal and cancerous lung cell lines. Gaydou et al 213 reported a lung tumor cell line invasiveness scale based on IR imaging based on a relative scale assigned to four different cell lines. These studies are important to pursue since they address the question of whether biochemical fate of cells and tissues can be predicted by early observations.…”
Section: Selected Applications Of Ir Chemical Imagingmentioning
confidence: 99%